Lessons in Theory of Change: Gender and Inclusion - Jost, Christine; Kristjanson, Patricia M.; Ferdous, N. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
Lessons learned from working with gender and social inclusion within the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS).